GUIANA - Geological and Metallogenic Environments of Gold Deposits of the Guiana Shield: A Comparative Study between St-Élie (French Guiana) and Omai (Guyana) - Jean Lafrance; Marc Bardoux; Gabriel Voicu; Ross Stevenson; Nuno Machado (Canadian Institute of Mining, Metallurgy and Petroleum, 1999)
"Abstract - Paleoproterozoic gold is found in two different volcano-sedimentary sequences and intrusive bodies separated by 600 km within the Guiana Shield. The 2148 Ma St-Élie granite intruded volcanic-arc sequences of the Paramaca Group, whereas the 2096 Ma Omai stock penetrated backarc/ island-arc sequences of the Barama-Mazaruni Group. Positive ?Nd values suggest that both suites lack Archean crustal contaminants, which is consistent with an origin in an oceanic arc setting.The St-Élie deposit is characterized by quartz-dominant vein systems with minor metallic minerals, represented chiefly by pyrrhotite and pyrite. Biotite, calcite, and chlorite are the main gangue minerals. The alteration haloes at St-Élie feature a strong potassic zone, which is absent at Omai. The ore-controlling structures are ductile and the vein emplacement is related mainly to contemporaneous, high-angle ductile shear zones. The St-Élie deposit formed at temperatures >350°C. The stable isotopes values are compatible with a magmatic or metamorphic source.The Omai deposit is characterized by quartz-dominant vein systems with minor metallic minerals, represented mainly by pyrite. Ankerite, scheelite, albite, and chlorite are common gangue minerals. The vein emplacement is syn- to post-deformation and it is related mainly to brittle shear zones with low-angle, stockwork networks and breccia zones. The Omai deposit formed in a temperature range between 250°C and 170°C, much lower than the St-Élie deposit. The stable isotope values are compatible with mixing between deep-seated fluids of metamorphic or magmatic origin with surface- derived fluids.These differences between St-Élie and Omai are interpreted in terms of their depth of formation. Alteration patterns, structural elements, and paragenetic assemblages indicate that the gold at St-Élie was most probably emplaced at a mesozonal depth, whereas the Omai setting yields evidence for epizonal conditions."